DESIGN EMPLOYEE DATA MANAGEMENT INFORMATION SYSTEM AT PT. SEMERU KARYA BUANA - Kristianto, Fesa Putra; Puspitaningsih, Fitri Indah; Salsabila, Sobrina Aisya (Politeknik ATI Padang, 2024)
The rapid development of technology in the era of globalization has led to significant advancements, with information systems being one of the innovations that facilitate information management. PT. X, a manufacturing company in the furniture sector, faced specific challenges in managing personnel administration, such as data input errors and payroll delays due to the use of conventional methods like Microsoft Excel. This resulted in inefficiencies and errors that affected the company's operations. This research designed an employee data management information system at PT. X with the aim of creating an effective and efficient system to assist administrators in processing employee data. The Rapid Application Development (RAD) method was used in the development of this system. The resulting application can be used by the HR department as administrators and by employees as users. The implementation results show that the new system effectively addresses the existing issues, with significant improvements such as reducing data input errors and increasing the speed of payroll processing compared to the previous method. From the user questionnaire results, both system quality and interface design received positive feedback, and the information system can be successfully applied at PT. X.